2018
DOI: 10.3390/w10111638
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Overland Flow through Rigid Emergent Vegetation with Different Densities and Location Arrangements

Abstract: The effect of vegetation density on overland flow dynamics has been extensively studied, yet fewer investigations have focused on vegetation arrangements with different densities and position features. Flume experiments were conducted to investigate the hydrodynamics of flow through rigid emergent vegetation arranged in combinations with three densities (Dense, Middle, and Sparse) and three positions (summit, backslope, and footslope). This study focused on how spatial variations regulated hydrodynamic paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Simulation of rigid vegetation is commone.g., in Stone & Shen 2002;James et al 2004;Meftah et al 2006;Kothyari et al 2009;Cheng & Nguyen 2011;Panigrahi 2015;Ahmed & Hady 2017;Chakraborty & Sarkar 2018;Wang et al 2018;and Tong et al 2019. (See Table 2).…”
Section: Experimental Programmentioning
confidence: 99%
“…Simulation of rigid vegetation is commone.g., in Stone & Shen 2002;James et al 2004;Meftah et al 2006;Kothyari et al 2009;Cheng & Nguyen 2011;Panigrahi 2015;Ahmed & Hady 2017;Chakraborty & Sarkar 2018;Wang et al 2018;and Tong et al 2019. (See Table 2).…”
Section: Experimental Programmentioning
confidence: 99%
“…Rigid vegetation and flexible vegetation showed significant differences in their influence on the hydraulic characteristics of slope flow. First, for rigid vegetation, the resistance to slope flow was greater because of its structural stability, especially in the flow rate, Reynolds number, and water depth increase; the total energy in the longitudinal position compared to bare slopes showed a fluctuating downward trend [24], indicating a stronger buffer capacity, which is conducive to reducing slope erosion and enhancing soil and water conservation. Moreover, rigid vegetation stem diameter exhibited significant resistance to surface runoff [22], and the resistance increased with increasing stem diameter [23].…”
Section: Effect Of Rigid and Flexible Vegetation On The Hydraulic Cha...mentioning
confidence: 99%
“…For example, the density of rigid vegetation is one of the key factors affecting the flow regime of slopes [20], and it directly determines the roughness of the slope surface: with the increase in vegetation cover, the slope velocity is correspondingly reduced, which decreases the water flow rate [21]. The stem diameter of rigid vegetation also exerts a significant drag effect on surface runoff [22], and the Darcy-Weisbach drag coefficient and vegetation stem diameter are proportional to the vegetation stem diameter, i.e., the larger the vegetation stem diameter, the greater the resistance to runoff [23], and rigid vegetation configured behind slopes is considered the best way to alter water flow conditions and reduce soil erosion [24]. When vegetation was submerged, the coefficient of water flow resistance was unusually sensitive to the change in flow regime [25], indicating that the presence of vegetation not only changed the physical characteristics of the slope but also significantly affected the kinetic characteristics of water flow.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Zhang et al (2017) found that the relationship between f and Re was not constant, and there was a critical coverage that made them appear differently correlated. The above research shows that the f–Re relation is affected by vegetation types and underlying surface conditions, which indicates that Re is not the only factor to predict the resistance coefficient (Wang et al, 2018). In fact, f is also affected by vegetation coverage (Li et al, 2013; Shang et al, 2020), stem diameter (Zhang et al, 2018; Zhao et al, 2015), slope gradient (Zhang, Liu, et al, 2019), and water depth (Baptist et al, 2010).…”
Section: Introductionmentioning
confidence: 99%